2021
DOI: 10.3390/jrfm14050222
|View full text |Cite
|
Sign up to set email alerts
|

Risk Spillover during the COVID-19 Global Pandemic and Portfolio Management

Abstract: This paper aims to examine the volatility spillover, diversification benefits, and hedge ratios between U.S. stock markets and different financial variables and commodities during the pre-COVID-19 and COVID-19 crisis, using daily data and multivariate GARCH models. Our results indicate that the risk spillover has reached the highest level during the COVID-19 period, compared to the pre-COVID period, which means that the COVID-19 pandemic enforced the risk spillover between U.S. stock markets and the remains as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 56 publications
(97 reference statements)
1
9
0
Order By: Relevance
“…Our results confirm that the COVID-19 pandemic increases the spillover effects and contagion among energy commodities, which, in turn, contribute to higher the level of systemic risk. These findings are in line with recent studies that show high correlations during the pandemic both in financial markets (Akhtaruzzaman et al 2021;Chevallier 2020;Yousfi et al 2021;Zaremba et al 2020;Zhang et al 2020) and in energy markets (Hauser et al 2020;Nyga-Łukaszewska and Aruga 2020). Moreover, our results suggest that the DAGM specification used in the multivariate models allows us to obtain more accurate estimates of the correlations (as also found in Candila 2021b) among commodities, and this highlights the presence of an asymmetric effect of COVID-19 on energy prices, as shown in Wang and Su (2021).…”
Section: Empirical Applicationsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results confirm that the COVID-19 pandemic increases the spillover effects and contagion among energy commodities, which, in turn, contribute to higher the level of systemic risk. These findings are in line with recent studies that show high correlations during the pandemic both in financial markets (Akhtaruzzaman et al 2021;Chevallier 2020;Yousfi et al 2021;Zaremba et al 2020;Zhang et al 2020) and in energy markets (Hauser et al 2020;Nyga-Łukaszewska and Aruga 2020). Moreover, our results suggest that the DAGM specification used in the multivariate models allows us to obtain more accurate estimates of the correlations (as also found in Candila 2021b) among commodities, and this highlights the presence of an asymmetric effect of COVID-19 on energy prices, as shown in Wang and Su (2021).…”
Section: Empirical Applicationsupporting
confidence: 92%
“…On one hand, we extended the current literature on the effects of the COVID-19 pandemic on the energy sector considering six energy commodities (West Texas Intermediate crude oil, Brent crude oil, Heating oil #2, Propane, New York Harbor Conventional Gasoline Regular, and Kerosene-Type Jet Fuel), whereas previous studies mainly focused on oil and natural gas (De Blasis and Petroni 2021;Gil-Alana and Monge 2020;Lin and Su 2021;Narayan 2020;Wang and Su 2021). On the other hand, we employed multivariate GARCH models in the energy sector (Chang et al 2011;Chkili et al 2014;Ku et al 2007;Silvennoinen and Thorp 2013;Yousfi et al 2021) within a risk management setting that, for the first time in this strand of literature, considers time series sampled at mixed-frequency. This allowed us to include the number of weekly deaths caused by the COVID-19 in the US for the estimation of daily volatilities and correlations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing between the two, our result demonstrates that bond market shock spillover has increased dramatically during Covid-19 period across maturities compared to pre-Covid-19 period. In the context of the financial market, Yousfi et al ( 2021 ) and Elsayed et al ( 2022 ) demonstrated that the shocks spillover had reached the highest level during the pandemic compared to the pre-pandemic period.…”
Section: Resultsmentioning
confidence: 99%
“…It, of course, reveals the devasting consequences of Covid-19 on sovereign bond markets around the world. Several recent studies, for example, Gubareva and Umar ( 2020 ), Zaremba et al ( 2021 ), Yousfi et al ( 2021 ) and Elsayed et al ( 2022 ), strongly argue that the Covid-19 pandemic affected financial markets severely.…”
Section: Resultsmentioning
confidence: 99%